The effects of water vapor on high temperature oxidation of Fe-Cr-Ni alloy at 1073k - Ani, Mohd Hanafi; Othman, Raihan (s.n., 2012)
Void formation in oxide scale during high temperature oxidation is a common phenomenon. Over a long period of time voids will affect the mechanical property of scales by influencing the cracking and spalling. Voids formed in dry environment are different than that of formed in humid environment. With the presence of water vapor in humid environment the formation of void will increase, thus greater number of void compared to that in dry environment